2018
DOI: 10.1038/s41598-018-23210-y
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal, temporal and trophic partitioning of flower-visitors in Alpine communities

Abstract: The cross-pollination of most alpine plants depends on insects, whose altitudinal distribution is limited by temperature. However, although global warming is causing shifts in temporal and spatial species distribution, we are still largely unaware of how plant-pollinator interactions change with elevation and time along altitudinal gradients. This makes the detection of endangered interactions and species challenging. In this study, we aimed at providing such a reference, and tested if and how the major flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 61 publications
7
66
3
Order By: Relevance
“…3) may increase the fitness of M. saniculifolia. The fact that M. saniculifolia (Han et al 2010) and flies (Kearns 1992;Lefebvre et al 2018) are both vulnerable to high temperature and desiccation should be considered in the conservation of this rare endemic plant under warmer and less snowy climate. However, we still know little about how significantly the flies affect M. saniculifolia's reproductive success.…”
Section: Temperature Impacts On Pollinator Assemblage and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…3) may increase the fitness of M. saniculifolia. The fact that M. saniculifolia (Han et al 2010) and flies (Kearns 1992;Lefebvre et al 2018) are both vulnerable to high temperature and desiccation should be considered in the conservation of this rare endemic plant under warmer and less snowy climate. However, we still know little about how significantly the flies affect M. saniculifolia's reproductive success.…”
Section: Temperature Impacts On Pollinator Assemblage and Activitymentioning
confidence: 99%
“…Such information helps infer possible changes in future pollinator assemblages and activity due to climate change (Hegland et al 2009). Recently, the global trend of rising temperatures has resulted in reduced pollinator abundance, which can threaten the survival of high-altitude plants that highly depend on them (Lefebvre et al 2018). Altitudinal scale investigation can be a good proxy for inferring the impact of temperature change on pollinator assemblage and activity as temperature varies with elevation (Hegland et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reviewed the richness of terrestrial insect species along elevational gradients (Hodkinson, ). Most such studies, which were conducted at 0–2,000 m, revealed a decreasing pattern of insect richness with elevation (Hanski, , in Indonesia; Wolda, , in Panama; McCoy, , in the southeastern United States; Perillo, Neves, Antonini, & Martins, , in tropical Brazil), or discovered a pattern that peaks at mid‐elevations (Gagne, , in Hawaii; McCoy, , in the southeastern United States; Lefebvre, Villemant, Fontaine, & Daugeron, , in the southern Alps, France). Insects are the main pollinators of flowering plants in general, regardless of whether they are generalists or specialists (Jacquemyn et al, ), thus it is reasonable to suspect that our finding on the decline in dioecy may be partially correlated with the change of insect pollinators along the elevational gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Machac, Janda and Dunn () studied phylogenetic patterns of ant species assemblages along an elevation gradient in three temperate montane systems, documenting contrasting patterns of overdispersion—suggesting competition—in ant communities at higher elevations, and clustering at lower elevations, suggesting environmental filtering likely driven by temperature in this case. Temperature is also one of the most important parameters segregating community assemblages in the temperate Alp Mountains for pollinating Diptera (Lefebvre et al., ) and for butterflies (Pellissier et al., ). In both cases, higher elevations entail lower temperatures that filter community assemblages, leading to the presence of closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Elevational gradients have been widely studied (Chatelain, Plant, Soulier‐Perkins & Daugeron, ; Lefebvre, Villemant, Fontaine & Daugeron, ; Lessard et al., ; Manel et al., ; McCain & Grytnes, ; Mouquet et al., ; Rahbek, , ; Sanders, Moss & Wagner, ), but incorporating phylogenetic information now allows to shed light on specific processes that shape the structure of communities along such gradients (Chazot et al., ; Graham & Fine, ; Graham, Parra, Rahbek & McGuire, ; Lessard et al., ; Manel et al., ; Pellissier et al., ). Indeed, over the last two decades, phylogenetic information has been increasingly incorporated into community ecology studies, either as a proxy for species’ ecological traits (ecophylogenetics, Webb, Ackerly, McPeek & Donoghue, ; Cavender‐Bares, Kozak, Fine & Kembel, ), to correct for non‐independence of co‐occurring species in the analyses of species’ traits (e.g., Losos et al., ) or to detect particular patterns, such as phylogenetically non‐random extinctions in communities driven by climate changes (Thuiller, Lavergne, Roquet, Boulangeat & Araujo, ).…”
Section: Introductionmentioning
confidence: 99%